Enterobius vermicularis (Nematoda: Rhabditida) at a rural school in the Córdoba province, Argentina: diagnosis and perception of parasitism - Cagnolo, Susana Raquel (2023)
Enterobius vermicularis is the causal agent of enterobiosis, a parasitic infection that primarily affects school-age children. This study aimed to achieve the following objectives due to the limited knowledge about prevalence of parasitic infections in the Córdoba region: to determine the prevalence of E. vermicularis in male and female students attending a rural primary school located in Sierras Chicas, Córdoba province, analyzing perianal and subungual samples; to investigate the correlation between the parasite presence and factors such as sex, age, and classroom; and, to assess the perception of parasitism based on symptoms, signs, and hygienic habits. Perianal samples were collected using the Graham method from a total of 37 students aged between 4 and 11 years old. Additionally, samples of the subungual region contents from both hands were also collected. A survey was conducted to gather information on both hygiene habits and symptoms from each school participant. The prevalence of E. vermicularis on perianal samples was 48.6%. However, no helminth eggs were detected in subungual samples. A correlation was observed between both the parasitic infection and children age. On the other hand, no significant association was observed between hygiene habits, symptoms reported by the students, and the parasitosis presence at the school population.